Studi Deskriptif Kepuasan Pelanggan terhadap Produk Metal Furniture Pada PPUPIK Politeknik Bosowa - burhan, imron; Sunding, Alang; ridhani, ulia (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2020)
This study aims to analyze the factors that influence customer satisfaction in purchasing metal furniture products at PPUPIK Polytechnic Bosowa. This research was conducted at PPUPIK Bosowa Polytechnic. The research method used is a quantitative method with data analysis techniques namely descriptive analysis. Research data were collected using a questionnaire instrument with a Likert scale to measure customer satisfaction in purchasing metal furniture products. The results showed that respondents' responses to aspects of product quality, service quality, and price indicate that the majority of customers answered strongly agree and agree. This shows that the majority of customers are satisfied with the product quality, service quality and prices from PPUPIK Polytechnic Bosowa.